Strategi Kepala Sekolah Meningkatkan Kompetensi Guru dalam Membuat Vidio Pembelajaran di SDN 01 Bukiklimbuku - Dewi Kurnia Putri; Suswati Hendriani (Pusat Pengkajian dan Pengembangan Sumber Daya Manusia (P3SDM) Melati, 2022)
The main problem facing education today is the quality of teachers as human resources and an important component in education development. Teachers should follow and have the capability the progress in science and technology in the era of globalization where competition quality being some things very urgent. Then the background of this research is the teacher problems using educational videos in the teaching and learning process that influence student interest. Every professional teacher should improve their personal quality in intellectual, spiritual, morality, creativity, and responsibility. This study aims to determine how the principal strategy for improving teacher competence in terms of pedagogical, professional, and quality personal and social. Furthermore, this study also aims to improve the competence of teachers to maximize the achievement of education that influence the result of the study by using interesting educational videos and media. This study uses a qualitative descriptive approach. In conclusion the principal strategy for improving the competence of teachers through empowerment by education supervisors. The strategy of the headmaster is needed for this problem.